Affectionate communication received from spouses predicts stress hormone levels in healthy adults - Floyd, Kory; Riforgiate, Sarah E. (My University, 2008)
Recent research on the communication of affection has illuminated its implications for mental and physical health. In particular, affectionate communication has been shown to covary with healthy hormonal variation and accelerated recovery from stress. The present study focuses on the association between marital affection and hormonal markers of stress regulation, including cortisol, dehydroepiandrosterone-sulfate (DHEA-S), and their ratio. Twenty healthy adults and their spouses provided independent reports of their propensity for verbal, nonverbal, and support-based expressions of affection prior to providing saliva samples that were assayed for cortisol and DHEA-S. As hypothesized, spouses’ reports of verbal, nonverbal, and supportive affection significantly predicted participants’ waking cortisol levels, cortisol change, and cortisol:DHEA-S ratio. Participants’ own reports of affection were predictive of cortisol:DHEA-S ratio for verbal affection behaviors only, and were not predictive of participants’ waking cortisol, cortisol change, or DHEA-S. In addition, spouses’ reports of verbal, nonverbal, and supportive affection predicted participants’ evening cortisol levels. Results illustrate that affectionate communication from one’s spouse is related to hormonal stress regulation and suggest the possibility that interventions designed to increase affectionate behavior in romantic relationships may have stress-ameliorating physiological effects.
Keywords: Affection; Stress; Affection exchange theory; Cortisol; DHEA-S